Analysis of Genetic Variation of MatK Gene Sequences in Ammothamnus lehmannii NCBI Popset 2440747918 Using In Silico RFLP - Dara Suci Amini; Afifatul Achyar (Genetikawan Muda Indonesia, 2023)
Genetic diversity or genetic variation is variation that occurs in an organism due to differences in the sequence of nucleotide bases (adenine, thymine, guanine and cytosine) that form DNA in cells. Variation genetics can be studied in silico using available gene sequences in the NCBI genbank database. This study used the MatK (Maturase-K) gene sequence with the identity number Popset 2440747918 which was downloaded in fasta format from NCBI . Then screening of restriction enzyme candidates was carried out to determine the restriction enzymes prior to in silico RFLP. The restriction enzyme selected from the screening was the restriction enzyme HindIII which has the recognition site A'AGC_T. The results obtained from 79 samples of DNA sequences, 76 samples were cut and 3 samples were not. And found three allele variations with the percentage of the presence of fragments A1 (86.07%), A2 (10.12%) and A3 (3.79%). The percentage values and frequencies of these A1, A2 and A3 alleles indicate a low level of genetic variation.